Проблеми, що виникають у процесі організації реконструкції будівель - Францкевич, С. Е. (Ways to Improve Construction Efficiency, 2012)
This article is dedicated to the revival of residential and non-residential fund of Ukraine. The problems arised during the organiziation of the reconstruction process of civil and industrial buildings and constructions were studied, as well as their solutions based on the analysis of domestic and international experience were represented.